Reciproc Blue x V-File: a study on the performance of two reciprocant instruments after third use (Research, Society and Development, 2021)
Objective: The cleaning and shaping of root canals is undeniably a step of great importance for the success of endodontic treatment. With the aim of optimizing the time and quality of this step, numerous instruments of different materials and shapes have been developed over the years. One of these instruments was nickel-titanium files, which have greater flexibility and resistance, allowing a better prognosis for endodontic treatment. In this study, two endodontic files, Reciproc Blue and V-File, were compared with the aim of evaluating their performance after the third use. Materials and methods: 60 acrylic blocks wrapped with laminated paper and filled with Nankin ink were used. Instrumentation was performed with an endodontic engine, by an experienced operator. After instrumentation, the blocks were photographed so that the photographs were superimposed. Results: After statistical analysis, it was found that there was no significant difference in the performance of the two groups after the third use. Conclusion: There was no significant difference between the two studied groups, and both are safe for the preparation of curved canals, but it is necessary that the manufacturer's recommendation is followed, regarding the number of canals instrumented with the same file.